PENINGKATAN KUALITAS DAN PRODUKTIVITAS KERAJINAN BORDIR DI DESA KETEGAN KECAMATAN TANGGULANGIN KABUPATEN SIDOARJO - Rina Sri Wulandari; Medya Ayunda Fitri; Yulia Tri Rahkadima (Universitas Nahdlatul Ulama Sidoarjo, 2018)
In 2016, Sidoarjo Regency became one of the districts with the highest number of SMEs. Embroidery is one of the results of its superior products, especially in the Tanggulangin area. However, currently Tanggulangin is only famous for bag craftsmen. Therefore, there is a need for assistance in boosting embroidery craft through a community partnership program (PKM). Some aspects of the problem that are prioritized in this program are aspects of production, product packaging, and marketing. From the aspect of production, the condition of partner production capacity 1 is still limited because partner 1 only has 1 embroidery machine. In addition, partner 1 does not have a soldering tool to punch holes in the applique. So the solution that will be given to the problem of the production aspect is to procure embroidery tools and production supporting equipment in the form of solder so as to maximize product preparation. The results achieved in this activity included labeling training, packaging, marketing and also machine purchases. Machine purchases are used to achieve the expected production capacity. The implementation of labeling and packaging training aims to make the products they market more attractive to consumers so they can increase the number of sales of their products. While online marketing training aims to make their products easier for the public to know.